Geological factors affecting the grade and tonnage of sandstone uranium deposits - Holliman, K A (Rhodes University, Faculty of Science, Department of Geology, 1981)
The largest known reserves of uranium are found in sandstone deposits, in the form of roll-front, peneconcordant and stacked types. Drilling on spacings of between 50 m and 5 m centres is the current method of attempting to delineate such ore bodies but because of the apparent random distribution of the mineralization there is a large degree of uncertainty in these predictions. Even on drilling grids of 3,5 m centres the uncertainty in predicting the distribution of stringer ore in roll front mineralization is still 100 per cent. (Sandefur & Grant 1980). Because of escalating costs it is becoming increasingly less economically feasible to delineate bodies of this nature in this manner and much more reliance will have to be placed on the geologist's interpretation of ore distribution when calculating ore reserves. The grade and tonnage of a sandstone uranium deposit can only be calculated with some degree of confidence if the processes forming the ore body are fully understood. The aim of this review is to examine the factors governing the formation and geometry of a sandstone body, the mobility and fixation of uranium and to establish criteria which will enable a more confident prediction to be made of the distribution of sand bodies and the distribution of the mineralization within them
Keywords: Uranium ores; Sandstone; Geology, Economic